John J. Crittenden papers - Crittenden, John J. (John Jordan), 1787-1863.
Correspondence, speeches, legal papers, and other papers. Chiefly correspondence covering Crittenden's career as U.S. attorney general and U.S. senator from and governor of Kentucky. Subjects include national politics, particularly banking and tariff matters, slavery, Mexico, and Texas; the southern Whigs; Crittenden's relations with Henry Clay; reactions to the Crittenden Compromise; and Kentucky politics and law. Correspondents include George Edmund Badger, Francis Preston Blair, Orlando Brown, Albert T. Burnley, Henry Clay, John M. Clayton, Charles Augustus Davis, Reverdy Johnson, Richard M. Johnson, Amos Adams Lawrence, Robert Perkins Letcher, C.S. Morehead, S.S. Nicholas, John S. Pendleton, Winfield Scott, Zachary Taylor, Robert Augustus Toombs, and Robert C. Winthrop.
Microfilm edition available in part
Microfilm produced from originals in the Manuscript Division.
U.S. attorney general and U.S. senator from and governor of Kentucky.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Badger, George Edmund, -- 1795-1866 -- Correspondence; Blair, Francis Preston, -- 1791-1876 -- Correspondence; Brown, Orlando, -- 1801-1867 -- Correspondence; Burnley, Albert T. -- Correspondence; Clay, Henry, -- 1777-1852.; Clay, Henry, -- 1777-1852 -- Correspondence; Clayton, John M. -- 1796-1856 -- Correspondence; Davis, Charles Augustus, -- 1795-1867 -- Correspondence; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Johnson, Richard M. -- 1781-1850 -- Correspondence; Lawrence, Amos Adams, -- 1814-1886 -- Correspondence; Letcher, Robert Perkins, -- 1788-1861 -- Correspondence; Morehead, C. S. -- 1802-1868 -- Correspondence; Nicholas, S. S. -- 1796-1869 -- Correspondence; Pendleton, John S. -- 1802-1868 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Taylor, Zachary, -- 1784-1850 -- Correspondence; Toombs, Robert Augustus, -- 1810-1885 -- Correspondence; Winthrop, Robert C. -- 1809-1894 -- Correspondence; United States. -- Department of Justice. -- Office of the Attorney General; Whig Party (U.S.); Banks and banking -- United States; Secession -- Southern States; Slavery -- United States; Tariff -- United States; Kentucky -- Politics and government -- 1792-1865.; Kentucky -- Politics and government -- 1865-1950.; Mexico -- History; Texas -- History; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; Cabinet officers; Governors -- Kentucky; Senators, U.S. Congress -- Kentucky